The effect of water absorption distribution of recycled coarse aggregate on the compressive strength distribution of high-performance concrete - Xiaoguang Chen; Elke Gruyaert; Özlem Cizer; Jiabin Li (Materiales de Construccion, 2023)
High water absorption is a typical characteristic of recycled coarse aggregate and is often used to explain the loss of performance of concrete when replacing natural coarse aggregate with recycled coarse aggregate. Extensive attention has been paid to the mean value of the water absorption of recycled coarse aggregate, but not to the standard deviation. This paper aims to assess whether recycled coarse aggregates with the same mean water absorption but different standard deviations will perform equally in high-performance concrete (HPC). The resulting HPC mixtures exhibited very similar compressive strength. Even so, it was hypothesised that as the standard deviation of the water absorption of recycled coarse aggregate increases over a wide range, the compressive strength of HPC will first increase due to local variations in the water/cement ratio, then decrease due to the presence of weak particles, and finally remain constant due to the role of the surrounding new mortar.